The Existentialist Critique of Freud : The Crisis of Autonomy - Izenberg, Gerald N., 1939- (Book collections on Project MUSE., 1976)
Although largely sympathetic to Freud's clinical achievement, the existentialists criticized Freudian metapsychology as inappropriate to a truly humanistic psychology. Gerald Izenberg evaluates the critique of Freud in the work of two existential philosophers, Martin Heidegger and Jean-Paul Sartre, and two existential psychiatrists, Ludwig Binswanger and Medard Boss.